Global Climate Services: A Typology of Global Decisions Influenced by Climate Risk - Bisaro, Alexander; Hinkel, Jochen; Le Cozannet, Gonéri; van der Pol, Thomas; Haas, Armin (Frontiers in Marine Science, 2021)
Climate services are ideally co-developed by scientists and stakeholders working together to identify decisions and user needs. Yet, while climate services have been developed at regional to local scales, relatively little attention has been paid to the global scale. Global climate services involve decisions that rely on climate information from many locations in different world regions, and are increasingly salient. Increasing interconnections in the global financial system and supply chains expose private companies and financial institutions to climate risk in multiple locations in different world regions. Further, multilateral decisions on greenhouse gas emission reduction targets, disaster risk finance or international migration should make use of global scale climate risk assessments. In order to advance global climate service development, we present a typology of decisions relying on global (i.e. non-local) climate risk information. We illustrate each decision type through examples of current practice from the coastal domain drawn from the literature and stakeholder interviews. We find 8 types of decisions making use of global climate information. At a top-level, we distinguish between 'multilateral climate policy decisions', and 'portfolio decisions involving multiple locations'. Multilateral climate policy decisions regard either 'mitigation targets' or 'multilateral adaptation' decisions. Portfolio decisions regard either 'choice of location' or 'choice of financial asset' decisions. Choice of location decisions can be further distinguished as to whether they involve 'direct climate risks', 'supply chain risks' or 'financial network risks'. Our survey of examples shows that global climate service development is more advanced for portfolio decisions taken by companies with experience in climate risk assessment, i.e. (re-)insurers, whereas many multilateral climate policy decisions are at an earlier stage of decision-making. Our typology thus provides an entry-point for global climate service development by pointing to promising research directions for supporting global (non-local) decisions that account for climate risks.